Handbook of research on electronic collaboration and organizational synergy - Salmons, Janet, 1952-; Wilson, Lynn, 1954- (Information Science Reference, 2009)
"This book presents a collection of empirical work that examines techniques, strategies and effects of electronic collaboration across disciplines and sectors"--Provided by publisher.